The Iraq Coup: A Historical Analysis - Atirah Afza (International Journal of Science and Society, 2023)
This scientific journal article presents a detailed and comprehensive analysis of a significant coup d'état in Iraq, aiming to shed light on the intricate web of historical, political, and socioeconomic factors that contributed to its occurrence and subsequent repercussions. Situated within the context of Iraq's turbulent history, this research examines the root causes, key actors, execution, consequences, and enduring legacies of the coup, with a particular focus on its regional implications.